Behavior Change Factors and Retention in Dietary Interventions for Older Adults: A Scoping Review. (3rd September 2021) - Zaslavsky, Oleg; Su, Yan; Kim, Boeun; Roopsawang, Inthira; Wu, Kuan-Ching; Renn, Brenna N
Abstract: Background and Objectives: Although poor diet is a major driver of morbidity and mortality in people aged 60 and older, few dietary interventions are widely implemented for this population. We mapped behavior change theories, agents, and techniques in dietary interventions for adults aged 60 and older and explored relationships between these factors and ability to retain at least 80% of the study participants. Research Design and Methods: We conducted a scoping review using MEDLINE, CINAHL, and Web of Science through April 2021 for dietary interventions in adults aged 60 and older. We collated, summarized, and calculated frequency distributions of behavior change theories, behavior change agents, and behavior change techniques (BCTs) using BCTv1 taxonomy with regard to participant retention across 43 studies. Results: Only 49% and 30% of the studies reported behavior theory and change agents, respectively. Of the studies reporting on theory and agents, the most common were social cognitive theory and the related mechanism of self-efficacy. The most common BCTv1 clusters were "shaping knowledge" and "goals and planning." Several BCTv1 clusters such as "antecedents" and "reward and threat" and evidence for concordance between BCTs and change agents were more common in interventions with higher retention rates. Discussion and Implications: Mechanistically concordant studies with BCTs that involve resource allocation and positive reinforcement through rewards may be advantageous for retention in dietary intervention for older adults. Future studies should continue developing theory and mechanism-oriented research. Furthermore, future studies should consider diversifying the portfolio of currently deployed BCTs and strengthening a concordance between BCTs and mechanisms of change.